Mixed convection flow of water conveying graphene oxide nanoparticles over a vertical plate experiencing the impacts of thermal radiation - Ishak, Anuar; Khan, Umair; Zaib, Aurang; Waini, Iskandar; Pop, Ioan (MDPI, 2022)
Water has drawn a lot of interest as a manufacturing lubricant since it is affordable, eco-friendly, and effective. Due to their exceptional mechanical qualities, water solubility, and variety of application scenarios, graphene oxide (GO)-based materials have the potential to increase the lubricant performance of water. The idea of this research was to quantify the linear 3D radiative stagnation-point flow induced by nanofluid through a vertical plate with a buoyancy or a mixed convection effect. The opposing, as well as the assisting, flows were considered in the model. The leading partial differential equations (PDEs) were transformed into dimensionless similarity equations, which were then solved numerically via a bvp4c solver. The influences of various physical constraints on the fluid flow and thermal properties of the nanofluid were investigated and are discussed. Water-based graphene oxide nanoparticles were considered in this study. The numerical outcomes indicated that multiple solutions were obtained in the case of the opposing flow (λ < 0). The critical values increased as the nanoparticle volume fraction became stronger. Furthermore, as the nanoparticles increased in strength, the friction factor increased and the heat transfer quickened. The radiation factor escalated the heat transfer in both solutions. In addition, a temporal stability analysis was also undertaken to verify the results, and it was observed that the branch of the first outcome became physically reliable (stable) whilst the branch of the second outcome became unstable, as time passed.